Implementation of Canva Training to Improve Digital Design Skills of Students and Teachers at SMA Nusa Bangsa Palembang - Muh Ridho Ardiansyah; Amelia Anggraini; Indah Rahma Sari; Andri Saputra; Mahmud (PT. Altaf Publishing Corp, 2026)
The development of digital technology requires students and teachers to have digital design skills that can support learning activities, school publication, and visual communication. Canva is one of the design platforms that is easy for beginners to use because it provides templates, visual elements, text editing features, color arrangement tools, and design export options. This activity aimed to improve the digital design skills of students and teachers at SMA Nusa Bangsa Palembang through practice-based Canva training. The method used a descriptive community service approach consisting of preparation, Canva introduction, poster design demonstration, participant practice, mentoring, poster output review, and reflection. The training was conducted at SMA Nusa Bangsa Palembang and involved students and teachers as participants. The training materials focused on creating school activity posters using Canva, including template selection, text editing, adding design elements, arranging color composition, and downloading the final design. The results showed that participants were able to follow the training process and produce a school activity poster containing important information such as the activity title, schedule, requirements, contact information, and supporting visual elements. This activity provided practical experience for participants in creating school publication media that were neater, more attractive, and more communicative. Therefore, Canva training can be considered a simple and applicable strategy to improve students’ and teachers’ digital design skills in the school environment.